Role of fluorodeoxyglucose-positron emission tomography/computed tomography in the evaluation of head and neck carcinoma - Moheieldin Abouzied; Ahmed Fathala; Abdulaziz Alsugair; Ahmad Al Muhaideb; Mohammed Al Qahtani (World Journal of Nuclear Medicine)
Fluorodeoxyglucose (FDG)-positron emission tomography-computed tomography (PET-CT) has been playing a pivotal role in tumor imaging for the past 20 years. Head and neck (HN) cancers are a good example that can illustrate such unique role of FDG imaging contributing to the patient's management. In this review article, we will describe the normal physiological distribution of FDG within HN structures focusing on its limitations and pitfalls. In addition, we will be also describing its role in the initial staging and restaging of the disease, particularly with regard to therapy response assessment. Furthermore, its role in the evaluation of patients with malignant cervical adenopathy from an unknown primary will be described. In 2016, the Royal College of Radiologists in its third edition published evidence-based guidelines for PET-CT use in HN cancer emphasizing its rule in all these clinical scenarios that are being described in this review. Finally, we will be highlighting future directions in the field of molecular imaging of HN tumors with a special emphasis on the new PET tracers.